How chromosome topologies get their shape: views from proximity ligation and microscopy methods. Issue 21 (3rd November 2020) - Huang, Yike; Neijts, Roel; de Laat, Wouter
Abstract : The 3D organization of our genome is an important determinant for the transcriptional output of a gene in (patho)physiological contexts. The spatial organization of linear chromosomes within nucleus is dominantly inferred using two distinct approaches, chromosome conformation capture (3C) and DNA fluorescent in situ hybridization (DNA–FISH). While 3C and its derivatives score genomic interaction frequencies based on proximity ligation events, DNA–FISH methods measure physical distances between genomic loci. Despite these approaches probe different characteristics of chromosomal topologies, they provide a coherent picture of how chromosomes are organized in higher‐order structures encompassing chromosome territories, compartments, and topologically associating domains. Yet, at the finer topological level of promoter–enhancer communication, the imaging‐centered and the 3C methods give more divergent and sometimes seemingly paradoxical results. Here, we compare and contrast observations made applying visual DNA–FISH and molecular 3C approaches. We emphasize that the 3C approach, due to its inherently competitive ligation step, measures only 'relative' proximities. A 3C interaction enriched between loci, therefore does not necessarily translates into a decrease in absolute spatial distance. Hence, we advocate caution when modeling chromosome conformations.